Micro/atomic-scale vibration induced superlubricity - Shuai Shi; Dan Guo; Jianbin Luo (Friction)
Abstract With the rapid development of industry, the inconsistency between the rapid increase in energy consumption and the shortage of resources is becoming significant. Friction is one of the main causes of energy consumption; thus, the emergence of superlubricity technology can substantially improve the energy efficiency in motion systems. In this study, an efficient method to control superlubricity at the atomic-scale is proposed. The method employs vibrational excitation, which is called vibration induced superlubricity (VIS). The VIS can be easily and steadily achieved by employing external vibration in three directions. The simple method does not depend on the type of sample and conductivity. Dependence of oscillation amplitude, frequency, scanning speed, and normal force (F N)on friction were investigated. Experimental and simulated explorations verified the practical approach for reducing energy dissipation and achieving superlubricity at the atomic-scale.